2018
DOI: 10.1016/s0140-6736(18)31771-9
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes after arthroscopic partial meniscectomy: a study of 700 000 procedures in the national Hospital Episode Statistics database for England

Abstract: SummaryBackgroundArthroscopic partial meniscectomy is one of the most common orthopaedic procedures worldwide. Clinical trial evidence published in the past 6 years, however, has raised questions about the effectiveness of the procedure in some patient groups. In view of concerns about potential overuse, we aimed to establish the true risk of serious complications after arthroscopic partial meniscectomy.MethodsWe analysed national Hospital Episode Statistics data for all arthroscopic partial meniscectomies don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 40 publications
8
65
0
Order By: Relevance
“…28 The largest age group in our study cohort was the 60-79-year age group and the 90-day mortality in the primary septic arthritis cohort in this age group was 7.39%, in comparison to 0.061% in the same period of time following arthroscopic partial meniscectomy, and 0.233% for the general population. 25 A diagnosis of osteoarthritis was also found to be associated with mortality in our cohort. In the unadjusted model, osteoarthritis was associated with increased odds of mortality, as has been previously observed for all cause and disease specific longer term mortality rates in other cohorts.…”
Section: Comparison With Other Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…28 The largest age group in our study cohort was the 60-79-year age group and the 90-day mortality in the primary septic arthritis cohort in this age group was 7.39%, in comparison to 0.061% in the same period of time following arthroscopic partial meniscectomy, and 0.233% for the general population. 25 A diagnosis of osteoarthritis was also found to be associated with mortality in our cohort. In the unadjusted model, osteoarthritis was associated with increased odds of mortality, as has been previously observed for all cause and disease specific longer term mortality rates in other cohorts.…”
Section: Comparison With Other Studiessupporting
confidence: 52%
“…A similar reduction in mortality over time has been observed for patients undergoing elective orthopaedic procedures. 24,25 In the present cohort, the fall in mortality may reflect a similar general improvement in healthcare, and outcomes could also have been influenced, in part, by initiatives such as the international "Surviving Sepsis" campaign and guidelines first published in 2004. 26,27 Older age and pre-existing joint disease have previously been shown to be poor prognostic factors for both joint outcome, mortality, and quality of life after an episode of septic arthritis in a small series of patients.…”
Section: Comparison With Other Studiesmentioning
confidence: 92%
“…Many (or even most) of the MRI tests and arthroscopies identified in our study may have been unnecessary. Although short term adverse events after knee arthroscopy are relatively rare, they may be serious and include venous thromboembolism (approximately five per 1000 procedures), infection (two per 1000 procedures) nerve damage (one per 1000) and death (<1 per 1000) . Longer‐term adverse effects may result from structural damage to the knee, with several studies based upon administrative data suggesting that arthroscopy in older adults may result in earlier need for knee joint replacement…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from a number of large, population‐based studies, the occurrence of VTE after knee arthroscopy is infrequent (<0.5%) for most patients. A recent UK National Health Service study of severe adverse outcomes of arthroscopic surgery in 700 000 patients described a 0.08% rate of any PE and a 0.001% rate of fatal PE within 90 days . A Kaiser Permanente study of more than 20 000 patients undergoing knee arthroscopy described a 0.25% rate of DVT and a 0.17% rate of PE .…”
Section: Risk Of Vte After Knee Arthroscopymentioning
confidence: 99%
“…Service study of severe adverse outcomes of arthroscopic surgery in 700 000 patients described a 0.08% rate of any PE and a 0.001% rate of fatal PE within 90 days. 27 A Kaiser Permanente study of more than 20 000 patients undergoing knee arthroscopy described a 0.25% rate of DVT and a 0.17% rate of PE. 28 An American College of Surgeons National Surgical Quality Improvement Program study (N = 12 271) found DVT rates of 0.46% and PE rates of 0.05% within 30 days after knee arthroscopy, 29 and a Mayo Clinic Olmsted County study (N = 4833)…”
Section: Quent (<05%) For Most Patients a Recent Uk National Healthmentioning
confidence: 99%